Nutrition labelling is a trade policy issue: lessons from an analysis of specific trade concerns at the World Trade Organization. (11th January 2017) - Thow, Anne Marie; Jones, Alexandra; Hawkes, Corinna; Ali, Iqra; Labonté, Ronald
Summary: Interpretive nutrition labels provide simplified nutrient-specific text and/or symbols on the front of pre-packaged foods, to encourage and enable consumers to make healthier choices. This type of labelling has been proposed as part of a comprehensive policy response to the global epidemic of non-communicable diseases. However, regulation of nutrition labelling falls under the remit of not just the health sector but also trade. Specific Trade Concerns have been raised at the World Trade Organization's Technical Barriers to Trade Committee regarding interpretive nutrition labelling initiatives in Thailand, Chile, Indonesia, Peru and Ecuador. This paper presents an analysis of the discussions of these concerns. Although nutrition labelling was identified as a legitimate policy objective, queries were raised regarding the justification of the specific labelling measures proposed, and the scientific evidence for effectiveness of such measures. Concerns were also raised regarding the consistency of the measures with international standards. Drawing on policy learning theory, we identified four lessons for public health policy makers, including: strategic framing of nutrition labelling policy objectives; pro-active policy engagement between trade and health to identify potential trade issues; identifying ways to minimize potential 'practical' trade concerns; and engagement with the Codex Alimentarius Commission to develop international guidance on interpretative labelling. This analysis indicates that while there is potential for trade sector concerns to stifle innovation in nutrition labelling policy, care in how interpretive nutrition labelling measures are crafted in light of trade commitments can minimize such a risk and help ensure that trade policy is coherent with nutrition action.